Application of a minerals, digestible amino acids and energy matrix to a broiler diet supplemented with a bacterial 6-phytase maintained growth performance and reduced feed costs compared to a minerals matrix alone - A. Bello; S. Haldar; A.E. Ghane; A. de Kreij; R. Hardy; Y. Dersjant-Li (Poultry Science, 2025)
The effect of stepwise application of a nutrient and energy matrix for a consensus bacterial 6-phytase variant (PhyG) to a corn-based diet, without or with xylanase-amylase-protease (XAP) supplementation, was evaluated in broilers. Day-old, Ross 308 males (2,400) were assigned to 8 treatments (10 replicate floor pens per treatment) in a randomized controlled block design. Diets were formulated in 4 phases and comprised: 1) nutritionally adequate control (PC); 2) negative control (NC1) reduced in Ca, digestible P and Na (by 0.22, 0.23 and 0.04 % points, respectively, vs. PC); 3) as NC1 but reduced in ME (by 72 to 51 kcal/kg; NC2); 4) as 3) reduced in digestible amino acids (AA) (by ≤ 0.06 % points vs. PC; NC3); 5), 6) and 7), as 2), 3) and 4) supplemented with PhyG at 1,250 phytase units (FTU)/kg (NC1+PhyG, NC2+PhyG and NC3+PhyG, respectively), and; 8) as 7) reduced in ME (by 61 kcal/kg), supplemented with XAP (2,000 xylanase units/kg, 200 amylase units/kg and 4,000 protease units/kg; NC4+PhyG+XAP). Orthogonal polynomial contrasts revealed linear and quadratic relationships (P < 0.05) between the degree of matrix applied and final (d 42) BW, overall ADG, average daily feed intake (ADFI), BW-corrected feed conversion ratio, d 21 tibia ash and tibia breaking strength. These measures were incrementally impaired with increasing matrix severity through PC, NC1, NC2 and NC3. Supplemental PhyG increased (P < 0.05) overall ADG and ADFI above the level of the respective NC, and maintained growth performance, tibia ash, breaking strength and carcass weights comparable to PC. Treatments NC3+PhyG and NC4+PhyG+XAP maintained all outcome measures at levels not different from the PC but with a lower estimated feed cost per kilogram BW gain than PC or NC1+PhyG (-0.039 USD/kg BW gain in NC3+PhyG vs. NC1+PhyG; P < 0.05). Application of a full nutrient and energy matrix with phytase can maintain growth performance and reduce feed costs compared with a minerals matrix alone.